INVENTARISASI POTENSI BUDAYA KAMPUNG NAGA SEBAGAI DAYA TARIK WISATA DI TASIKMALAYA - , FERA YULIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kampung Naga is a village inhabited by a group of people who are very firm hold relics of ancestral customs. Kampung Naga located in the District Neglasari Salawu Tasikmalaya regency. Final Task is about the potential of culture into a tourist attraction in the Kampung Naga and the Role of the Government and People of the Kampung Naga as a tourist attraction in Tasikmalaya. With the purpose to determine the potential of Kampung Naga culture of today and what has been developed in Kampung Naga, a tourist attraction in Tasikmalaya and find out how much the role of government and the community in the conservation of cultural Kampung Naga, who has appeal as a supporting element development of tourism. This research was conducted in Kampung Naga retrieval using observation data, interviews, documentation, library research and data analysis. The conclusion that can be drawn from this study that the potential of culture in Kampung Naga is located in the settlement patterns, architectural buildings, traditions and art, while the government has a limited role only manage the development of facilities and infrastructure, the role of the community become a very important position as one of the requirements of planning, management and development.